Women and Values in the Vortex of Objectivity: Sharon L. Crasnow's Contribution to the Feminist Discussion of Philosophy of Science - Haekal Pradifa Furqon (West Science Social and Humanities Studies, 2024)
This study investigates Sharon L. Crasnow's perspective on the philosophy of science, specifically exploring its compatibility with feminist ideals. Crasnow introduces her notion of model-based objectivity as a reaction and expansion of the principles advocated by feminist empiricism, postmodernism, and Harding and Wylie's feminist standpoint viewpoint theory. Crasnow holds the belief that there is an inherent connection between science and value. The efficacy of grounding in scientific endeavor and the development of epistemic virtues depend on specific societal principles, such as acknowledging and appreciating women's contributions in scientific discussions. Feminism is not considered a dedicated adherence to a particular set of beliefs or ideology. Instead, people view feminism as a mindset or a critical scientific perspective. According to Crasnow, the best way to understand natural reality is to use a model to achieve a clear and objective understanding. The procedure entails identifying specific values that lay the groundwork for modeling. These values are evaluated by considering pragmatic variables and maximizing the achievement of goals. In this context, objectivity refers to the validation of a value based on its ability to improve people's lives to the fullest extent. This enhances the model's capacity to serve as a means of accomplishing it.